Dialog Kehidupan Ibu Teresa dalam Konteks Memoria Passionis dan Pluralitas Agama di India - Sugiarto, Bernardus Ario Tejo (Jurnal Orientasi Baru, 2012)
People in general and Asian people in particular think that Christianity has close relation with western colonialism. This opinion is based on their historical experience. In middle ages, in fact, Christianity had arrived in Asia together with colonialism and Christianity was also the only belief of coloniser. The experience of colonization has hurt Asian people heart so deeply that it can’t be forgotten. Up to now, this memoria passionis always rise hatred and vengeance not only to western nations but also to Christianity. In this context, Mother Teresa has chosen and lived an appropriate dialogue to do her mission of charity in India. It is dialogue of life, the dialogue that flow out from the deep faith and love of Jesus Christ into human life.